THE EXISTENCE OF GOOD GOVERNMENT GOVERNANCE LPSE AGAINST CONSPIRACY BY BUSINESSES IN PROCUREMENT OF GOODS AND SERVICES (INFRASTRUCTURE) IN PROTECTING THE INTEREST OF STAKEHOLDER - Yetti; Onasis D. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Good Government Governancein Electronic Procurement Services (LPSE) was created to reduce fraud, one of which is against conspiracy carried out by business Actors in the procurement of goods and services. The purpose of this research is to analyze the problems in the existence of Good Government Governance of Electronic Procurement Services (LPSE) against conspiracy conducted by business actors in the procurement of goods and services and to analyze the implementation of existing laws and regulations in providing penalties for perpetrators who commit conspiracy practices in project tenders. The method of this research is sociological law. The existence of Good Government Governance in Electronic Procurement Services (LPSE), still provides opportunities for conspiracy by business actors in the procurement of goods and services. It has not been able to meet expectations because of Human Resources, Technical Difficulties, and Funding Sources. The existence of Good Government Governance in Electronic Procurement Services (LPSE), apparently has not contained and provided the information needed by the community and is not yet transparent. The existence of Good Government Governance in Electronic Procurement Services (LPSE) has not been able to avoid the disputes made by business actors in the procurement of goods and services. It was found in the field research that the disputes could result in the project being not environmentally friendly and could neglect the interests of the local community. Recommendations: There is a need for coordination from each SKPD so that the e-tender carried out can be optimized. LPSE Pekanbaru City always makes various efforts so that the realization of e-tender as a process of procurement of goods and services that can be well implemented.